Probiotics for the treatment of depression and its comorbidities: A systemic review - Gao, Jie; Zhao, Longyou; Cheng, Yiwen; Lei, Wenhui; Wang, Yu; Liu, Xia; Zheng, Nengneng; Shao, Li; Chen, Xulei; Sun, Yilai; Ling, Zongxin; Xu, Weijie (Frontiers in Cellular and Infection Microbiology, 2023)
Depression is one of the most common psychiatric conditions, characterized by significant and persistent depressed mood and diminished interest, and often coexists with various comorbidities. The underlying mechanism of depression remain elusive, evidenced by the lack of an appreciate therapy. Recent abundant clinical trials and animal studies support the new notion that the gut microbiota has emerged as a novel actor in the pathophysiology of depression, which partakes in bidirectional communication between the gut and the brain through the neuroendocrine, nervous, and immune signaling pathways, collectively known as the microbiota-gut-brain (MGB) axis. Alterations in the gut microbiota can trigger the changes in neurotransmitters, neuroinflammation, and behaviors. With the transition of human microbiome research from studying associations to investigating mechanistic causality, the MGB axis has emerged as a novel therapeutic target in depression and its comorbidities. These novel insights have fueled idea that targeting on the gut microbiota may open new windows for efficient treatment of depression and its comorbidities. Probiotics, live beneficial microorganisms, can be used to modulate gut dysbiosis into a new eubiosis and modify the occurrence and development of depression and its comorbidities. In present review, we summarize recent findings regarding the MGB axis in depression and discuss the potential therapeutic effects of probiotics on depression and its comorbidities.